Meningitis with septic shock resulting from odontogenic infection misdiagnosed as closed-lock in temporomandibular disorder: A case report and literature review - Yoshizawa, Kunio; Hanihara, Mitsuto; Harada, Daiki; Myose, Natsuhiko; Sakata, Hiroki; Moriguchi, Takeshi; Moroi, Akinori; Ueki, Koichiro (Medicine (Baltimore), 2023)
Infections that spread to the pterygomandibular muscle can be misdiagnosed as temporomandibular disorder (TMD) because of the resulting difficulty in opening the mouth. Importantly, infection of the pterygomandibular space can extend to the skull base in the early stages, and a delay in therapeutic intervention can lead to severe complications. A 77-year-old Japanese man with trismus after pulpectomy was referred to our department. This case report describes a rare instance of meningitis with septic shock caused by an odontogenic infection, initially misdiagnosed as TMD due to similar symptoms, leading to life-threatening complications. The patient was diagnosed with sepsis and meningitis resulting from cellulitis in the pterygomandibular space caused by iatrogenic infection after pulpectomy of the right upper second molar. After emergency hospitalization, the patient developed septic shock and required blood purification. Subsequently, abscess drainage and extraction of the causative tooth were performed. However, the patient developed hydrocephalus secondary to meningitis and underwent ventriculoperitoneal shunting to alleviate the condition. The infection was controlled and the patient level of consciousness improved following treatment for hydrocephalus. The patient was transferred to a hospital for rehabilitation on the 106th day of hospitalization. Infections of the pterygomandibular space may be misdiagnosed as TMD, owing to the main symptoms of restricted mouth opening and pain on mouth opening. A prompt and appropriate diagnosis is crucial because these infections can lead to life-threatening complications. A detailed interview, along with additional blood tests and computed tomography (CT) scans, can aid in making an accurate diagnosis.